Critical appraisal of systematic reviews on the effect of a history of periodontitis on dental implant loss - Faggion Junior, Clóvis Mariano; Giannakopoulos, Nikolaos Nikitas (Journal of clinical periodontology, 2013)
Objective To perform a systematic critical appraisal of the methodological quality of systematic reviews on the effect of a history of periodontitis on dental implant loss. Materials & Methods PubMed, the Cochrane database for systematic reviews, the DARE, Biosis Preview, CINAHL, Web of Science, and LILACS electronic databases were searched on 16th June 2012, independently and in duplicate, for systematic reviews and meta-analyses related to dental implants for patients with and without a history of periodontitis. Manual searching of the reference lists of included papers was also conducted. The methodological quality of these systematic reviews was assessed by use of the AMSTAR and R-AMSTAR checklists. Before quality assessment was initiated, the reviewers were calibrated until they achieved excellent agreement. Results Sixty-eight papers were initially retrieved. Of these, nine systematic reviews and three meta-analyses were included. Some domains, for example, “characteristics of the included studies” were satisfied in both checklists. In contrast, domains such as “comprehensive literature search” and “assessment of likelihood of publication bias” were rarely met. Conclusion Much methodological variability was encountered in the selected reviews. To furnish readers with a more comprehensive assessment of the evidence, authors should observe higher standards when conducting and reporting their reviews.
Gesehen am 25.02.2021